Implementation of Religious Tolerance Values in Islamic Religious Education Learning (Study at SD Negeri 253 Bangko) - Habib Ilham Kholiq; Afriandi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research is aimed to investigate in this research to know how the implementation of the values of religious tolerance in PAI learning at SD Negri 253 Bangko, The support and inhibiting factors and how the implementation of the values of religious tolerance in learning PAI at the school. This research is a qualitative descriptive method with a phenomenological approach. Data collection in this research is the observation, in-depth interviews, documentation, and triangular. While analyzing data is obtained by the researcher using reduction data, presentation data and verification data. The result of the research shows that the implementation of the values of religious tolerance in PAI learning at SD Negri 253 Bangko is done by 1) Giving an opportunity to all students to follow the teaching of religion based on their religion, 2) Creating a tolerant climate in each lesson ( learn the different, creating an mutual trust, maintaining an mutual understanding, Revering an mutual love). 3) Make deeper related the material ( values of tolerance). The supporting factors including The government policy that has given the rules about embed the values of tolerance among religions, There is adequate facilities, the establishment of cooperation between the school community in religious activities. As for the inhibiting factors including the level of ability, The students have a different an emotional maturity, the school lacks educators Kristenism, the school lacks facilities (instructional media), limited time in learning. The success of the implementation of the values of religious tolerance in PAI learning is all the students who Moslem able to work together without discriminating against religion. The students have a high faith (religious), the students and teachers can be tolerance for each other, the students and teachers have a democratic character, The creation of harmony and good solidarity.